Sosialisasi Stunting Sebagai Upaya Peningkatan Peran Orang Tua Dalam Pencegahan Kurang Gizi Pada Balita Di Desa Bayung Gede - Putu Pande R. Aprilyani Dewi; I Gusti Ayu Agung Pramita Indraswari; Ni Putu Budiadnyani (JURNAL PENGABDIAN MASYARAKAT AKADEMISI, 2023)
Human Resources are the main requirement to bring this country to become a developed Indonesia. However, the preparation of these resources is constrained by the problem of stunting. Stunting cases in Bangli Regency have a high number where Bayung Gede Village is included in the list of villages that have mild stunting zones, namely the number of cases at 20 percent to 30 percent. One of the causes of stunting is a lack of nutritional intake. So, it is necessary to hold socialization and education related to stunting in Bayung Gede Village. The activity took place for two days on Thursday and Friday, 27-28 October 2022 which took place at the Bayung Gede Village Hall. This activity was attended by PKK women. The socialization provided succeeded in making PKK mothers understand the importance of nutrition in toddlers and the importance of planning a pregnancy.